The Role of NG2 Proteoglycan in Glioma - Sridevi Yadavilli (Translational Oncology, 2016)
Neuron glia antigen-2 ((NG2), also known as chondroitin sulphate proteoglycan 4, or melanoma-associated chondroitin sulfate proteoglycan) is a type-1 membrane protein expressed by many central nervous system (CNS) cells during development and differentiation and plays a critical role in proliferation and angiogenesis. ‘NG2’ often references either the protein itself or the highly proliferative and undifferentiated glial cells expressing high levels of NG2 protein. NG2 glia represent the fourth major type of neuroglia in the mammalian nervous system and are classified as oligodendrocyte progenitor cells by virtue of their committed oligodendrocyte generation in developing and adult brain. Here, we discuss NG2 glial cells as well as NG2 protein and its expression and role with regards to CNS neoplasms as well as its potential as a therapeutic target for treating childhood CNS cancers.